2005
DOI: 10.1111/j.1365-2427.2005.01440.x
|View full text |Cite
|
Sign up to set email alerts
|

Net heterotrophy in Faroe Islands clear‐water lakes: causes and consequences for bacterioplankton and phytoplankton

Abstract: 1. Five oligotrophic clear-water lakes on the Faroe Islands were studied during August 2000. Algal and bacterial production rates, community respiration, and CO 2 saturation were determined. In addition, we examined the plankton community composition (phytoplankton and heterotrophic nanoflagellates) and measured the grazing pressure exerted by common mixotrophic species on bacteria. 2. High respiration to primary production (6.6-33.2) and supersaturation of CO 2 (830-2140 latm) implied that the lakes were net … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Our results are in agreement with several studies that have suggested that respiration exceeds photosynthesis in the epilimnion of oligotrophic lakes (del Giorgio & Peters, 1994;Duarte & Agustí, 1998;Pålsson et al, 2005;Simčič, 2005;Karlsson et al, 2007). del Giorgio & Peters (1994) reported that plankton community respiration was 2-to 8-fold greater than phytoplankton photosynthesis in oligotrophic and mesotrophic lakes during the growing season, but that this imbalance decreased in the more productive lakes.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Our results are in agreement with several studies that have suggested that respiration exceeds photosynthesis in the epilimnion of oligotrophic lakes (del Giorgio & Peters, 1994;Duarte & Agustí, 1998;Pålsson et al, 2005;Simčič, 2005;Karlsson et al, 2007). del Giorgio & Peters (1994) reported that plankton community respiration was 2-to 8-fold greater than phytoplankton photosynthesis in oligotrophic and mesotrophic lakes during the growing season, but that this imbalance decreased in the more productive lakes.…”
Section: Discussionsupporting
confidence: 95%
“…Primary production by phytoplankton, macrophytes, and benthic algae forms the autochthonous basis of the food web. Terrestrial input of particulate and dissolved organic carbon is a potential allochthonous basis of the food web (Cole et al, 2000;Pålsson et al, 2005). Ecosystems in which photosynthesis exceeds total respiration (P [ R) are net autotrophic-they are net sinks for CO 2 and net producers of O 2 and organic matter.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, mixotrophy tends to be a suitable strategy in environments with low nutrients and good light climate (i.e. oligotrophic clear lakes), thus mixotrophs tend to dominate over strictly autotrophic organisms due to their capability to incorporate nutrients by prey ingestion (Medina-Sa ´nchez et al, 2004;Pa ˚lsson et al, 2005). On the other hand, in environments with humic coloured waters characterized by relatively low Kd values and high a 320 absorbances, the mixotrophic flagellates that are able to turn from autotrophy to heterotrophy to supplement their carbon budget under light limitation may thrive.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship of BPr : PPr with Chl a was generally more variable (r 2 5 0.42), especially in our more oligotrophic reservoirs, than would be expected from the strong relationships of BPr and PPr with Chl a (r 2 5 0.84 and 0.89, respectively). In their study of oligotrophic lakes on the Faroe Islands, Palsson et al (2005) found that areal BPr : PPr also ranged widely (0.21-0.95). The higher variance of BPr : PPr in more oligotrophic systems could be caused by bottom-up control of BPr, whereas top-down control may be more common in eutrophic systems.…”
Section: Discussionmentioning
confidence: 99%